Penilaian Kinerja Reksa Dana Saham di Indonesia Ketika Pasar Naik dan Turun Tahun 2007 – 2009 - Kongdro, Handrich; Handoyo, Sarwo Edy (Journal of Business Strategy and Execution, 2012)
Mutual funds had become an investment alternative for the Indonesian people who wanted to invest in the stock market but have limited knowledge, money, and time. But it is not easy anyway to determine which mutual funds can be a good option for investors, especially in the type of mutual fund shares that have the highest rate of return at the same risk as compared to other types of mutual funds. Recorded in 2007, JCI continued to rise significantly throughout the year, but in 2008 had a significant reduction is also due to the supreme case of mortgage and again increased in 2009 which exceeded the increase in 2007. In market conditions that rise and fall like that assessment of the performance of mutual fund shares using the method of Sharpe, Treynor and Jensen. The results showed that 9 out of 30 equity funds have consistently performing above the market's performance during 2007 to 2009, the equity funds Fortis Equity, Primary Shares, Prima Equity Fund, First State Indoequity Sectoral Fund, Mandiri Investa Attractive, Equity Funds mainstay, Bahana Prima Fund, Schroder Plus Achievement Fund, and Aggressive Investment NAM.